Comparison of fixed and adaptive directional microphone in starkey hearing aid using myhint - Hong, Lim Chu (Universiti Sains Malaysia, 2016)
This study aimed to compare the effectiveness of fixed and adaptive directional microphone (DM) when the noise was presented from front using Malay Hearing in Noise Test (MyHINT). DM is a feature that increase the speech recognition by achieving better signal to-noise ratio. Ten subjects, who were using Malay as first language, with bilaterally to-noise ratio. Ten subjects, who were using Malay as first language, with bilaterally symmetrical mild to severe sensorineural hearing loss with no hearing aid using experience were recruited from Hospital USM. Four sets of sentences in MyHINT were presented using free field after fitted with Starkey Z series i70 behind-the-ear style hearing aids bilaterally. The speech was presented either from the front or right side of the subject. The findings of this study showed that performance of adaptive DM had no significant difference from fixed DM when the speech was presented from the front. However, there was significant difference of adaptive DM from fixed DM when the speech was presented from the right side. There was no significant difference of speech recognition performance no matter speech sound was presented from front or right side of subject using fixed DM. However, significant difference was shown when speech was presented from right side than front of the subject using adaptive DM. In conclusion, the findings of this study suggested that even when the noise presented from the front, the adaptive DM did provide the benefits to hearing aid users when the speech at the different direction from noise.